Political Reorientation of Farmer-Based National Food Law in Realizing Food Sovereignty - Parnoko Parnoko; Endang Sutrisno (Jurnal Legisci, 2026)
Background. The main problem lies in the mismatch between legal norms that promise farmer protection and policy practices that are still oriented towards market stability and food security. Aims. This study aims to analyze the political direction of national food law in relation to farmer partisanship and formulate a farmer-centric policy reorientation model to realize food sovereignty. Methods. The research uses a juridical-socio-legal approach with a qualitative, descriptive-analytical method, drawing on literature on laws and regulations, academic literature, and empirical data on food policy dynamics. Result. The results of the study show that the politics of national food law is still dominated by the supply-oriented, market-driven paradigm, so that farmers are not positioned as the main subjects in the food system. The current food security approach has limitations in addressing structural problems, such as unequal access to resources, weak price protection, and low farmer participation in the policy process. This condition has an impact on the fact that food sovereignty has not been realized substantially. Conclusion. As a solution, this study offers a political reorientation of farmer-based food law that emphasizes strengthening farmers' position through regulatory reformulation, economic protection, and increased participation in policymaking. Implementation. This approach is expected to shift the paradigm of food law from simply ensuring availability to a just, sustainable, and sovereign system. Thus, food law not only functions as a regulatory instrument but also as a means of empowering farmers in realizing national food welfare and independence.